Sporadic sodium and E layers observed during the summer 2002 MaCWAVE/MIDAS rocket campaign - Williams, B. P.; Croskey, C. L.; She, C. Y.; Mitchell, J. D.; Goldberg, R. A. (Annales Geophysicae, 2006)
On 5 July 2002, a MaCWAVE (Mountain and Convective Waves Ascending VErtically) payload launched from Andøya Rocket Range, Norway, observed narrow enhanced layers of electron density that were nearly coincident with sporadic sodium layers measured by the Weber sodium lidar at the nearby ALOMAR Observatory. We investigate the formation mechanism of these layers using the neutral wind and temperature profiles measured directly by the lidar and the vertical motion deduced from the sodium mixing ratio. Through comparisons of the lidar data to the sporadic E in situ data, we find support for the concentration and downward motion of ions to an altitude where chemical models predict the rapid conversion of sodium ions to neutral sodium.